High-oxygen modified atmosphere package improves color stability of Longissimus lumborum with high ultimate pH from pasture-fed Nellore bulls - Ribeiro, Caio César de Sousa (2017)
Red bright color is an important quality attribute that influences beef purchasing and is affected by beef pH. Therefore, the aim of this study was to determine if high ultimate pH affected color stability of longissimus lumborum (LL) steaks from pasture-fed Nellore bulls and if HiOx atmosphere package improved the color stability of high pHu muscles. To achieve these objectives, 18 LL muscles from Nellore bulls were grouped into 3 pHu ranges: normal (n = 6; 5.40 < pHu <5.79), intermediate (n = 6; 5.80 < pHu <6.19) and high (n = 6; pHu > 6.20). All the muscles were cut into 2.5 cm steaks and packaged in 80% O2/ 20% CO2 (v/v) and then stored at 2 ± 1 ºC under dark conditions until day 5 and under fluorescent light until day 14 (the end of display-time). pH, gas composition, instrumental color, surface pigment, metmyoglobin reducing activity (MRA), oxygen consumption rate (OCR), and lipid oxidation were determined throughout display-time. High pHu steaks were darker (L*), redder (a*, a*/b*), with better tone (Hue), less metmyoglobin and higher MRA (p < 0.05) than normal pHu samples. HiOX MAP increased surface OMb during display time in pHu > 6.2 (p < 0.05), showing a bright-red color in high group. Intermediate group was less dark than high group and had longer color stability than normal group (p < 0.05). Therefore, High pHu had great color and lipid oxidation stability and desired color due to HiOx MAP under cold storage for 14 days and intermediate pHu had beneficial aspects presented in both other treatments.